Parent’s Involvement in Children’s English Literacy Skills - Hemas, Made Diana Ayu; Padmadewi, Ni Nyoman; Dewi, Putu Eka Sulistya (STKIP AGAMA HINDU SINGARAJA, 2023)
The current study aimed at investigating parental involvement in developing children’ English literacy skill. This study was a descriptive qualitative conducted in Aura Sukma Insani school Bali. To conduct the study, questionnaire, interview and observation were employed. The results showed that the parental involvement programs in Aura Sukma Insani Bilingual Kindergarten were parents conference, parents’ interview, final report, and eco-enzyme. The specific programs which involved parents applied four out of six parental involvement frameworks proposed by Epstein et al., (2002). Parenting was applied through giving parents’ guidance book about the learning process. Then, decision making was applied through asking parents’ decision about learning which will be applied. During the implementation of parental involvement programs, A number of problematic challenges exist in the parents' involvement implementation at Aura Sukma Insani Kindergarten. According to the interpretation level of the teacher's perspective, decision-making and collaborating with the community had the most problematic Challenges. Overall, the teachers faced at least one to two challenges in every type of involvement. The problems mostly came from fewer responses obtained due to the less effective activities. This imperfection could be fixed if these two pasties, the parents and the school, recognized their interchangeable roles were important.